1987
DOI: 10.1080/00268978700100491
|View full text |Cite
|
Sign up to set email alerts
|

I.R. laser chemistry of allyl phenyl ether

Abstract: The Claisen rearrangement of allyl phenyl ether to 2-allyl phenol has been investigated by I.R. multiphoton excitation. While the thermal reaction of the same starting material yields only the Claisen isomerization product, the I.R. photochemical excitation initiates both fragmentation and isomerization reactions. The dependence of product distribution on fluence is different at various wavelengths. Two mechanisms are proposed for the I.R. photochemical reaction. One assumes selective absorption, the other ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Nevertheless, such wavelength-selective IR laser induced chemical reactions were observed in the gas phase. 93 Finally, the results of Figure 6 also reveal that the exposure sensitivities are essentially independent of spiropyran concentrations; this indicates that the intermolecular merocyanine interactions and/or the degree of aggregate formation do not play a significant role within the concentration range that we considered.…”
Section: Recording In the Irmentioning
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, such wavelength-selective IR laser induced chemical reactions were observed in the gas phase. 93 Finally, the results of Figure 6 also reveal that the exposure sensitivities are essentially independent of spiropyran concentrations; this indicates that the intermolecular merocyanine interactions and/or the degree of aggregate formation do not play a significant role within the concentration range that we considered.…”
Section: Recording In the Irmentioning
confidence: 69%
“…It must be noted that, with organic solids, it is extremely difficult to measure differences in vibrational excitation and relaxation processes, because the intermolecular energy dissipation is normally dominant. Nevertheless, such wavelength-selective IR laser induced chemical reactions were observed in the gas phase . Finally, the results of Figure also reveal that the exposure sensitivities are essentially independent of spiropyran concentrations; this indicates that the intermolecular merocyanine interactions and/or the degree of aggregate formation do not play a significant role within the concentration range that we considered.…”
Section: Recording In the Irmentioning
confidence: 69%
“…This is partially because intramolecular vibrational energy redistribution (IVR) dissipates the deposited energy fast to other modes before the reaction arises. , Alternatively, if a dominant (nonstatistical) IVR pathway exists due to the coupling between an excited vibrational mode and a reaction coordinate, this might be exploited to induce a desired chemical transformation in an elegant and selective way. , One remarkable example illustrating this possibility is the vibrationally induced unimolecular reaction of the jet-cooled Criegee intermediate syn -CH 3 CHOO, reported by Lester and co-workers The authors demonstrated that excitation of CH stretching overtones or combination modes induces a 1,4-H shift from the methyl group to the terminal oxygen and activates decomposition of the molecule (Scheme ). Nevertheless, the application of this strategy to induce and control organic reactions remains scarcely explored. …”
mentioning
confidence: 99%
“…As reported, the phenolic compounds containing alkenyl side chains undergo alkenyl elimination steps to remove their side chains in thermal reaction. 44,45 Therefore, the Ph may originate from the elimination of alkenyl side chains of intermediates. At 280 °C under 0 MPa H 2 , the alkenyl elimination reaction was favorable because the hydrogenation of alkenyl side chains into alkyl side chains not readily occur, thus promoting the formation of Ph.…”
Section: Repolymerizationmentioning
confidence: 99%
“…The elimination of side chains seems not through the cleavage of C-C linkages on the Ni (220H) catalyst, as the 2D-HSQC NMR analysis results demonstrated that the cleavage of C-C linkages was suppressed under 0 MPa H2. As reported, the phenolic compounds containing alkenyl side chains undergo alkenyl elimination step to remove their side chains in thermal reaction44,45 . Therefore, the Ph may originate from the elimination of alkenyl side chains of intermediates.…”
mentioning
confidence: 92%